Synthesis and Research of Coordination Compounds of Co (II), Ni (II), Cu (II) Salts with 2-(3- Hydroxypropyl) Benzimidazole - Ergasheva R.U.; Rakhmonova D. S. (Genius Journals, 2022)
A method for the synthesis of complex compounds of metals with 2-(3-Hydroxypropylbenzimidazole acetates, chlorides and nitrates of Co(II), Ni(II) and Cu(II)has been developed method for the synthesis of complex compounds of metals with 2-(3-Hydroxypropylbenzimidazole acetates, chlorides and nitrates of Co(II), Ni(II), Cu(II), aswell as analysis of the composition and structure of synthesized complex compoundsusing modern physicochemical methods using IR spectroscopy and EDH analyses hasbeen developed. It was found that the ligand 2-(3-Hydroxypropyl) benzimidazole iscoordinated through a nitrogen atom in the imidazole ring in complexation reactions., aswell as analysis of the composition and structure of synthesized complex compoundsusing modern physico-chemical methods using IR spectroscopy and EDH analyses. It wasfound that the ligand 2-(3-Hydroxypropyl) benzimidazole is coordinated through anitrogen atom in the imidazole ring in complexation reactions
Keywords: 2-(3-gidroksipropyl) benzimidazole, salts, elektrodonor atom, ligand, IR-spectroscopy, EDH analysis, monodentate, bidentate binding